2019
DOI: 10.5089/9781498320498.001
|View full text |Cite
|
Sign up to set email alerts
|

Regional Growth Spillovers in Sub-Saharan Africa

Abstract: This paper documents the steady increase in intraregional trade in sub-Saharan Africa since 1980, links this rise to important growth spillovers in the region, and identifies the main source countries and those most vulnerable to the economic conditions of others. Estimates show that in the short run, positive idiosyncratic shocks to regional trading partners’ growth significantly increase growth in the average sub-Saharan African country, while in the long-run the annual impact of growth in regional trading p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Within sub‐Saharan Africa (SSA), on account of regional integration, Arizala et al . () concurs by finding that a 1 per cent shock in average growth of trading partners is associated with an increase of about 0.5 per cent in output of the average SSA country 4 years after the shock.…”
Section: Review Of Literaturementioning
confidence: 52%
See 1 more Smart Citation
“…Within sub‐Saharan Africa (SSA), on account of regional integration, Arizala et al . () concurs by finding that a 1 per cent shock in average growth of trading partners is associated with an increase of about 0.5 per cent in output of the average SSA country 4 years after the shock.…”
Section: Review Of Literaturementioning
confidence: 52%
“…In accordance with Agenda 2063, the AfCFTA aims to create a single continental market for goods and services (TRALAC, ). The AfCFTA is expected to enhance competitiveness at the industry and enterprise level through exploitation of opportunities for scale production, market access and better reallocation of resources (TRALAC, ; Arizala et al ., ). By reducing the trade costs and increasing access to diversified products, the AfCFTA is expected to improve the competitiveness of downstream industries who can access cheaper raw materials and intermediate inputs.…”
Section: Introductionmentioning
confidence: 97%
“…Through this, the AfCFTA aims to establish a single continental market for goods and services, hence providing larger market access. By providing freer markets, the AfCFTA is also expected to promote competitiveness at all value chains in production processes at the industry and enterprise levels through exploitation of opportunities for scale production and improved resource reallocation (Arizala, Bellon, & MacDonald, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Measured as a share of total exports, SSA exhibits the highest share of intra-regional trade integration among emerging and developing economies with the sub-regional trade agreements-particularly SADC and the EAC-playing a major role in strengthening bilateral trade in the region (Arizala et al, 2019). Thus, for most part, while evidence abounds on the sub-regional trade agreements spurring trade, empirical studies on the trade effects of a continental-wide trade agreement, such as AfCTFA, is dearth although few studies are notable.…”
Section: Introductionmentioning
confidence: 99%
“…They further found that there was no trade diversion for imports from outside the region. Within sub-Saharan Africa (SSA), on account of regional integration, Arizala et al (2019) concurs by finding that a 1 per cent shock in average growth of trading partners is associated with an increase of about 0.5 per cent in output of the average SSA country 4 years after the shock. The study found that creation of COMESA, ECOWAS and SADC led to a significant increase in trade among member states while creation of ECCAS had dampened both intra-ECCAS and extra-ECCAS bilateral trade flows.…”
Section: Empirical Literaturementioning
confidence: 89%